Pseudotetraploa sexualis sp. nov., a lignicolous freshwater fungi from Wenshan, Yunnan Province, China - Liu, Ting-Xiang; Wang, Wen-Peng; Shen, Hong-Wei; Luo, Zong-Long; Feng, Yuan (Phytotaxa, 2026)
Lignicolous freshwater fungi are a highly diverse group that play an important role in freshwater ecosystems. During the investigation of species resources of lignicolous freshwater fungi in the Wenshan Autonomous Prefecture, Yunnan Province, a sexual fungus was isolated from submerged decayed wood. Based on morphological observations and phylogenetic analysis of combined LSU, ITS, SSU, and tub2 sequence data, a new species, Pseudotetraploa sexualis sp. nov., is proposed. Notably, this represents the first sexual morph reported for the genus Pseudotetraploa, distinguished by its semi-immersed to immersed, subglobose to globose ascomata with a cylindrical beak; peridium composed of textura angularis to textura prismatica cells; filamentous, septate pseudoparaphyses; bitunicate, fissitunicate, 8-spored, clavate to cylindric-clavate asci with a rounded apex and an ocular chamber; narrowly fusiform, hyaline to olive-brown, uniseptate, guttulate ascospores with acute or obtuse ends, surrounded by a mucilaginous sheath. A detailed description and illustration of the species are provided herein.